Weaponized social media - Gordon, Sherri Mabry (Critical thinking about digital media, 2019)
Originally conceived as a way for people to stay connected, share photographs and post information, social media has evolved. Today, it is much more than a fun communication tool, it can become a destructive weapon when exploited by the wrong people. This book explains the benefits of social media, how social media is being used as a weapon, who is weaponizing social media and why, and what readers can do to protect themselves. Includes a glossary and references.-- Publisher's website.